Sistem Informasi Bank Sampah Dalam Meningkatkan Ekonomi dan Pengendalian Dampak Lingkungan di Desa Kota Pari - Muttaqin, Muhammad; Yusup, Mohammad; Syaula, Maya; Widodo, Arif Arya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Pari City Waste Bank application utilizes a computerized system in managing waste involving the field of information technology. This shows that information technology has become a supporting part in managing waste management. This waste bank is a village institution that operates in the field of waste processing. Apart from saving and sorting waste, the waste bank also teaches people to process waste into items that are useful and have selling value. A computerized system is needed in waste bank institutions so that performance can improve and the institution can develop better. From the existing problems, the author created a system for transactions and management of the Waste Bank in Pari City using a web-based information system. The results of this web-based Waste Bank application can speed up and make it easier for officers to carry out transactions, process and record customer savings data at the waste bank.